KONSTRUKSI PEMBELAJARAN KYAI MLANGI DAN RELEVANSINYA BAGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Suwadi Suwadi (Jurnal Pendidikan Agama Islam, 2012)
Individual research article aims to present a clear picture of the learning Kyai Mlangi construction and relevance for lslamic learning (PAI) in school. Setting location of a community school in Mlangi, Northwest city of Yogyakarta in Yogyakarta Nagari Pathok Mosque complex, which consists of 13 boarding school. After participant observation, in-depth interviews and qualitative analysis, the conclusion that; the first one, learning construction Kyai Mlangi mapped into three types (1) the child-nurse Pype, (2) the parent type, and (3) the grandparent type. Type of Learning Ny. Khunah close to the child-nurse type with a tendency of learning bequeathed a sense of satisfaction in female students when he was able to memorize or read the Qur 'an correctly and fluently. Meanwhile Kyai H. Munahar, Kyai Wirdanuddin and Gus Jfik closer to the parent type Kyai where all three are likely to have committed and skilled to teach and bring new ideas to the students. Parody, jokes, and even tried to evoke imagery Kyai gradually a success oriented students. Than Kyai Suja'i conservated the grandparent type with characteristics similar to the approach of a philosopher and a little attention to the material Kyai Sufism. The second one, the construction of learning Kyai Mlangi learning value. more emphasison the value of the substance (matter) itself. The third one, construction Kyai Mlangi learning is relevant to learning nilia PAI values education in schools such as patience, diligence, obedience, discipline and example through a method that dibelajarkan through proverbs and uswah hasanah.